The Diaries of Anthony Hewitson, Provincial Journalist Volume 1: 1865-1887 - Hobbs, Andrew (Open Book Publishers, 2022)
Anthony Hewitson (1836-1912) was a typical Victorian journalist, working in one of the largest sectors of the periodical press, provincial newspapers. His diaries, written between 1862 and 1912, lift the veil of anonymity hiding the people, processes and networks involved in the creation of Victorian newspapers. They also tell us about Victorian fatherhood, family life, and the culture of a Victorian town. Diaries of nineteenth-century provincial journalists are extremely rare. Anthony Hewitson went from printer's apprentice to newspaper reporter and eventually editor of his own paper. Every night he jotted down the day's doings, his thoughts and feelings. The diaries are a lively account of the reporter's daily round, covering meetings and court cases, hunting for gossip or attending public executions and variety shows, in and around Preston, Lancashire. Andrew Hobbs's introduction and footnotes provide background and analysis of these valuable documents. This full scholarly edition offers a wealth of new information about reporting, freelancing, sub-editing, newspaper ownership and publishing, and illuminates aspects of Victorian periodicals and culture extending far beyond provincial newspapers. The Diaries of Anthony Hewitson, Provincial Journalist are an indispensable research tool for local and regional historians, as well as social and political historians with an interest in Victorian studies and the media. They are also illuminating for anyone interested in nineteenth-century social and cultural history.